Ambidextrous leadership and its role in achieving organizational superiority: an analytical study of the opinions of a sample of heads of scientific departments in public universities in the Kurdistan Region of Iraq - Ali , Nizar; Ismael , Hadi; Yousif , Mehvan (Humanities Journal of University of Zakho, 2023)
The current research aims to identify the role of Ambidextrous leadership in its three dimensions (open leadership behaviors, closed leadership behaviors, and flexible leadership behaviors) in achieving organizational superiority in its five dimensions (strategic planning, the focus on operations, the focus on the work force, information and analysis, and business results), with an analytical study of the opinions of a sample of heads of scientific departments in public universities in the Kurdistan Region of Iraq, and the sample was (340) people. The questionnaire was used as a means to obtain data, as the research adopted the descriptive analytical approach in its procedures, and used in the research a set of statistical means (arithmetic mean, standard deviation, simple correlation matrix and simple regression analysis), and depending on the software package (SPSSV.25), and accordingly a hypothetical chart was designed that shows the correlation and impact relationships between the main research variables and its dimensions. One of the most prominent conclusions reached by the research is the existence of a correlation and high levels of morale between Ambidextrous leadership and organizational superiority at the total and partial levels, as the more the universities researched focus on Ambidextrous leadership, the more this leads to upgrading organizational superiority towards the distinguished educational services provided by universities to the beneficiaries of their services. According to the conclusions, a number of proposals were put forward, the most important of which is that those in charge of the surveyed universities are keen to conduct surveys of the services provided by competitors and the requirements of the beneficiaries of their services and benefit from the results by including them in their strategies to enhance the value that enables them to sustain Ambidextrous leadership and behaviors, as well as providing an advanced infrastructure that facilitates the performance of universities for their work and enables them to achieve organizational superiority.